COMPARISON OF TWO FORMULAS TO CALCULATE THE ULTRASOUND FETAL WEIGHT VS. BIRTH WEIGHT - Fiestas, Carlos (2015)
OBJETIVE: To compare if either Hadlock (1985) or Lagos formulas to calculate fetal weight correlates better with newbom weight. DESING: Prospective study. MATERIAL AND METHODS:- Fifty pregnant women had ultrasound study at Cayetano Heredia Piura Hospital trom March to May 2003 in order to measure biparietal diameter (BPD), femur length (FL), abdominal perimeter (AP) and head circumference (HC). Fetal weight was estimated and compared with newbora weight (NW). Correlation was calculated between HadIock and Lagos curves, and newborn weight. RESUlTS.: Mother age averaged 26,9 ±6,3 years. Newborn weíght averaged 3210 g. For HadIock, estimated fetal weight averaged 3 207 g, error 5,54%, standard error 130 g and correlation 0,887. For Lagos, estimated fetal weight averaged 3 259 g, error 5,75%, standard error 142 g and correlation 0, 871. CONCLUSION.- The most reliable formula to estimate fetal weight is that proposed by HadIock.